La capacitación como eje de desarrollo del sector público localizado en Quito. - Perugachi Caiza, Diana Carolina (2016)
This paper starts from the analysis of the need to increase ongoing training for the improvement of the development of the public sector. The purpose of this research conceptualizes the ongoing training as an axis of development for the public sector located in Quito, this research examine the methodology, processes / actions used to strengthen and make learning strategies automatic for public employees. Based on the study, it is possible to identify the number of public employees, job classification (according to records provided by the Ministerio de Finanzas), and the identification of training needs. This research shows the effort Ecuadorian government is doing in order to strengthen of training programs. The purpose of the government is to make public management more efficient so that public employees and the country as well develop within the concept of a knowledge – based society through original strategies of technological scientific education and professional teaching